2005
DOI: 10.1177/1051228404274307
|View full text |Cite
|
Sign up to set email alerts
|

Dotlike Hemosiderin Spots Are Associated With Past Hemorrhagic Strokes in Patients With Lacunar Infarcts

Abstract: Our findings suggest that many deep dotHSs on T2(*)-weighted magnetic resonance imaging may be correlated with deep ICH-lacunar infarction type of SVD recurrence but not lacunar infarction-lacunar infarction type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…In several series, CT detected rapid hematoma expansion within 6 hours of onset. 1,3,4 In this study, we measured the maximal diameter of deep ICH on CT after more than 6 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) hours. An important goal of this study was to detect the relationship between dotHSs and the maximal diameter of deep ICH.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In several series, CT detected rapid hematoma expansion within 6 hours of onset. 1,3,4 In this study, we measured the maximal diameter of deep ICH on CT after more than 6 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) hours. An important goal of this study was to detect the relationship between dotHSs and the maximal diameter of deep ICH.…”
Section: Discussionmentioning
confidence: 99%
“…8,10,18,19,26,27 Our previous studies demonstrated that dotHSs may be associated with deep ICH rather than lacunar infarction on the basis of SVD recurrence. 19 Several clinical investigations revealed that dotHSs were correlated with the tendency to bleed after stroke. 14,15 We hypothesized that dotHSs might be associated with a large size of deep ICH.…”
Section: The Tendency To Bleedmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6]8,13 Subcortical MB may arise from amyloid angiopathy, particularly in older patients. 6,7 However, both deep and subcortical MB are associated with the recurrence of small-vessel disease including deep ICH and lacunar infarction. [4][5][6] In addition, the number of subcortical MB is linearly related to the number of deep MB.…”
Section: The Number Of Mbmentioning
confidence: 99%
“…6,7 However, both deep and subcortical MB are associated with the recurrence of small-vessel disease including deep ICH and lacunar infarction. [4][5][6] In addition, the number of subcortical MB is linearly related to the number of deep MB. 4-6 Therefore, we did not differentiate between MB in these locations in this study.…”
Section: The Number Of Mbmentioning
confidence: 99%